Phytoextraction du cuivre par l’Atriplex canescens (Pursh)Nutt. dans un milieu salin, étude des paramètres biométriques et biochimiques de la plante - TADJOURI, HOURIA; BLALTA, KARIMA; LAYADI, FATIMA ZOHRA (My University, 2016)
Since the industrial revolution, the intensification of polluting activities contributed to the contamination of soil and it is extending to the planetary scale. Considering this phenomenon, some plants developed, the ability to accumulate contaminants in their tissues. Although it is only very recently that phytoremediation which is designated as the techniques using plants to extract, degrade or immobilize contaminants present in the soil. The strong accumulation of salts in soils as well as in irrigation water greatly disrupts the growth and development of almost all plants. The study of its disruption in halophytes helps bring better guidance on the deleterious effect of salinity and heavy metals. Our study on the phytoextraction of copper in saline soil by the halophyte plant Atriplex canescans (push) nutt belonging to Chenopodiaceae family cultivated in a controlled greenhouse of Mazagran station (Wilaya of Mostaganem). The experiment was conducted using saline-based NaCl (0.5%) and 3% and copper sulfate CuSO45H2O (2000, 2500 and 3000 ppm) separately and combined. The aim was to monitor and measure the influence and the effect of metal and salt stress on biochemical and biometric parameter. The results showed that Atriplex canescens (push) Nutt is resistant to copper excess salinity up to 2000 and 3000pp; and 30g/l NaCl. It was also recorded as the metal salt and stress have led biometric disturbance significantly affecting the lengths of stems, leaf area and also the root volume and the concentration of chlorophyll. While the study of the biochemical behaviour of the plant, the results showed an increase of proline and soluble sugars in the leaf system and especially where a combination of the two salts were used.
Keywords: phytoextration; Atriplex canescens (pursh) nutt; cuivre; salinité; paramétré biochimique; biométrique; Copper; Salinity; biochemical parameter; biometric; النباتات المعالجة; النحاس; الملوحة; المؤشرات البیوكیمیائیة; المؤشرات البیومتریة.